2011
DOI: 10.1016/j.compositesa.2011.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tool geometry and numerical parameters when modeling orthogonal cutting of LFRP composites

Abstract: The first objective of this paper is to analyze the influence of mesh size and shape in finite element modeling of composite cutting. Also the influence of the level of energy needed to reach complete breakage of the element is considered. The statement of this level of energy is crucial to simulate the material behavior. On the other hand geometrical characteristics of the tool have significant influence on machining processes. The second objective of the present work is to advance in the knowledge concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 29 publications
9
57
0
1
Order By: Relevance
“…By comparing with FEM model, the EFG model under-estimated the forces at lower angles and overestimated them at higher angles. This could be attributed to the different failure mechanisms that are adopted between this study (maximum stress) and that used in [17] i.e. Hashin.…”
Section: Meshfree Set Up and Pre-processingmentioning
confidence: 99%
See 4 more Smart Citations
“…By comparing with FEM model, the EFG model under-estimated the forces at lower angles and overestimated them at higher angles. This could be attributed to the different failure mechanisms that are adopted between this study (maximum stress) and that used in [17] i.e. Hashin.…”
Section: Meshfree Set Up and Pre-processingmentioning
confidence: 99%
“…The concept of degrading the stiffness of the composite in certain directions has been used in study composites failure including machining of composites [11,15,17]. In this study, the stiffness degradation values were adopted from [47] and are shown in Table 2.…”
Section: Stiffness Degradationmentioning
confidence: 99%
See 3 more Smart Citations